2019
DOI: 10.1016/j.envres.2019.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Wood dust and urinary 15-F2t isoprostane in Italian industry workers

Abstract: Wood dust is one of the most common occupational exposures, with about 3.6 million of workers in the wood industry in Europe. Wood particles can deposit in the nose and the respiratory tract and cause adverse health effects. Occupational exposure to wood dust has been associated with malignant tumors of the nasal cavity and paranasal sinuses. The induction of oxidative stress and the generation of reactive oxygen species through activation of inflammatory cells could have a role in the carcinogenicity of respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…15-F 2t -IsoP is a widely used biomarker of exposure [21,41]. Therefore, it is of primary importance to understand its biological relevance in terms of health risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15-F 2t -IsoP is a widely used biomarker of exposure [21,41]. Therefore, it is of primary importance to understand its biological relevance in terms of health risk.…”
Section: Discussionmentioning
confidence: 99%
“…Significant associations between occupational air pollution exposure and increments of biomarker exposure and cancer risk are apparent [16,17,18,19]. Recently, we have examined the prevalence of urinary 15-F 2t isoprostane (15-F 2t -IsoP), a biomarker of oxidant status [20], in woodworkers compared to controls in Tuscany, Italy [21]. In that study, we found a significant excess of urinary 15-F 2t -IsoP excretion in woodworkers with an overall Means Ratio (MR) of 1.36, 95% C.I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FA may directly originate from natural sources, from several anthropogenic activities and from indirect product via the photochemical oxidations of hydrocarbons in the atmosphere [8,9]. FA has been detected in several occupational settings involving wood-based materials, laminates, paints and urea-based resins [10] and is used as disinfectant and preservative in hospitals and in pathology units [11]. According to the International Agency for Research on Cancer (IARC) [12] and the United States Environmental Protection Agency (US EPA) [13], FA is classified as a human carcinogen.…”
Section: Introductionmentioning
confidence: 99%
“…This cross-sectional study aims to evaluate the role of FA exposure and the urbanisation level on OS induction, quantified by urinary 15-F2t-Isoprostane (15-F2t-IsoP), and on airway inflammation, measured by the fraction of exhaled nitric oxide (FeNO). It is notable that 15-F2t-IsoP is a reliable and sensitive biomarker of OS, used in several other epidemiological studies [10,11,16]. FeNO is measured in a non-invasive way and is a biomarker of eosinophilic airway inflammation, useful in monitoring inflammatory processes due to air pollution exposure [20].…”
Section: Introductionmentioning
confidence: 99%